Genome-wide Linkage Analysis of Carotid Artery Lumen Diameter: The Strong Heart Family Study - Bella, Jonathan N. (2013)
BACKGROUND: A significant proportion of the variability in carotid artery lumen diameter is attributable to genetic factors. METHODS: Carotid ultrasonography and genotyping were performed in the 3,300 American Indian participants in the Strong Heart Family Study (SHFS) to identify chromosomal regions harboring novel genes associated with inter-individual variation in carotid artery lumen diameter. Genome-wide linkage analysis was conducted using standard variance component linkage methods, implemented in SOLAR, based on multipoint identity-by-descent matrices. RESULTS: Genome-wide linkage analysis revealed a significant evidence for linkage for a locus for left carotid artery diastolic and systolic lumen diameter in Arizona SHFS participants on chromosome 7 at 120 cM (lod=4.85 and 3.77, respectively, after sex and age adjustment, and lod=3.12 and 2.72, respectively, after adjustment for sex, age, height, weight, systolic and diastolic blood pressure, diabetes mellitus and current smoking). Other regions with suggestive evidence of linkage for left carotid artery diastolic and systolic lumen diameter was found on chromosome 12 at 153 cM (lod=2.20 and 2.60, respectively, after sex and age adjustment, and lod=2.44 and 2.16, respectively, after full covariate adjustment) in Oklahoma SHFS participants; suggestive linkage for right carotid artery diastolic and systolic lumen diameter was found on chromosome 9 at 154 cM (lod=2.72 and 3.19, respectively after sex and age adjustment, and lod=2.36 and 2.21, respectively, after full covariate adjustment) in Oklahoma SHFS participants. CONCLUSION: We found significant evidence for loci influencing carotid artery lumen diameter on chromosome 7q and suggestive linkage on chromosomes 12q and 9q.